(untitled) (Scientific journal of the Fergana State University, 2025)
The article analyzes the positive attitude of Ishakhan Ibrat, the son of Junaidullahkhoja from Turakurgan, one of the descendants of Khoja Ahmed Yasawi, a fighter for independence, a public figure, an enlightened poet, a scientist and publicist, a progressive educator, as well as the creative and creative work of a thinker.